83: phoenixin-14 ameliorates cholestatic liver injury and bileinduced acute pancreatic injury in rats - KAHRAMAN, MERVE MERİÇ; YÜKSEL, MERAL; YEGEN, BERRAK; ERCAN, FERİHA (My University, 2022)
Background: Bile duct obstruction, which results in cholestatic liver injury, is also the major cause of acute pancreatitis. Phoenixin (PNX) was originally defined as a hypothalamic peptide associated with a wide range of physiological processes and exerts antioxidant and antiinflammatory effects. PNX is expressed in several peripheral organs including pancreas and liver. We aimed to evaluate possible therapeutic effects of PNX on hepatic and pancreatic damage induced by biliary or pancreaticobiliary duct obstruction. Methods: In male Sprague Dawley rats, bile duct ligation (BDL; n=16) or pancreaticobiliary duct ligation (PBDL; n= 16) was performed under ketamine anesthesia, while control rats (n=8) had sham-surgery. Either PNX-14 (50 µg/kg/day) or saline was subcutaneously injected immediately after surgery and in the following 2 days. On the post-operative 3rd day, hepatic and renal blood flow was measured using laser Doppler flowmeter under anesthesia and the rats were then euthanized. In the liver and pancreas samples, levels of malondialdehyde, antioxidant glutathione and myeloperoxidase activity were measured by spectrophotometry, while luminol- and lucigenin-enhanced chemiluminescence (CL) levels were measured to assess formation of reactive oxygen species (ROS). Tissue samples were stained by hematoxylin-eosin to calculate microscopic damage scores. Statistical analyses were made by one-way ANOVA. Results: Increased microscopic damage scores in the pancreas of saline-treated PBDL (p<0.001) and in the liver of saline-treated BDL group (p<0.001) were reduced by PNX14 treatment (p<0.01), but PBDL-induced hepatic damage (p<0.001) was not changed by PNX-14. Pancreatic and hepatic levels of malondialdehyde and myeloperoxidase activity and pancreatic glutathione levels were not different among the experimental groups, while hepatic glutathione level was elevated in PNX-14-treated BDL (p<0.001) and PBDL (p<0.01) groups as compared to control group. Despite a non-significant fall in renal or hepatic blood flow in saline-treated BDL rats, PBDL significantly reduced hepatic (p<0.001) and renal (p<0.01) blood flow, while PNX-14 reversed blood flow in both organs back to control levels (p<0.05). The CL levels of luminol and lucigenin were increased in both hepatic and pancreatic tissues of saline-treated BDL and PBDL groups (p<0.05-0.001), showing enhanced ROS generation. However, CL levels in both the liver and pancreas of PNX-14-treated BDL and PBDL groups were significantly reduced as compared to those measured in the liver and pancreas of respective saline-treated groups (p<0.05-0.001). Conclusion: In conclusion, cholestatic liver injury and bile-induced pancreatic injury are alleviated by PNX-14 treatment, which appears to act via its ROS scavenging activity, by replenishing hepatic antioxidant capacity and restoring impaired organ perfusion.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Fizyoloji; Medicine; Health Sciences; Fundamental Medical Sciences; Human Physiology; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; TIP, GENEL & DAHİLİ; FİZYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MEDICINE, GENERAL & INTERNAL; PHYSIOLOGY; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Fizyoloji (tıbbi); Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Physiology (medical); Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Physiology; Life Sciences